#TITLE_ALTERNATIVE# - SUJATMIKO (NIM 20195504), PONCO
If A : X -- Y is a linear compact operator on Hilbert space X, Y with dim (X) is not finite dimension then the linear compact operator A can not have a continuous inverse. We wish to approximate the solution (p to the equation Ap = f from knowledge of a perturbed right hand side f 6 with known error level II f - f 6II < 6, i.e., we want <p6 to depend continuously on the data f 6. Therefore our task requires finding an approximation of the unbounded invers operator A-1 : A (X) -- X by a bounded linear operator Ra : Y --- X.